Study of Porosity and Surface Groups of Activated Carbons Produced from Alternative and Renewable Biomass: Buriti Petiole - de Almeida, Cristiane Freitas; de Andrade, Robson Carlos; de Oliveira, Giulyane Felix; Suegama, Patrícia Hatsue; de Arruda, Eduardo José; Texeira, José Augusto; de Carvalho, Cláudio Teodoro (Orbital: The Electronic Journal of Chemistry, 2017)
This study reports the production of activated carbon (AC) from chemical activation with sodium hydroxide in pyrolysis temperature of 500 to 600 °C using alternative and renewable material, Buriti petiole. The characterization of the material was performed by simultaneous thermogravimetry-differential thermal analysis (TG–DTA), scanning electron microscopy (SEM), nitrogen adsorption–desorption isotherms at -196 °C by the BET (Brunauer, Emmett and Teller) and BJH (Barrett, Joyner and Halenda) methods for mesoporous materials. Infrared spectroscopy (FT–IR) and TG/DT–FTIR coupled system were used to study the surface groups. Adsorption tests for the activated carbons samples (ACs) were carried out using the methylene blue (MB) cationic and anionic orange G (OG) dyes, the most satisfactory results were methylene blue dye. These results indicated the formation of mesoporous adsorbent materials with BET surface areas obtained between 340 m2g-1 and 1715 m2g-1. The chemical activation of the carbons with sodium hydroxide produced highly mesoporous material suitable for adsorption of cationic and anionic dyes in aqueous solution. DOI: http://dx.doi.org/10.17807/orbital.v9i1.878